Government Expenditure Efficiency Towards Islamic Human Development Index (IHDI): Data Envelopment Analysis Application - Fahmi Alhadi; Achmad Firdaus; Zulkarnain Muhammad Ali (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2024)
This study examines the efficiency of local government spending in 34 provinces in Indonesia against the indicators of the Islamic Human xDevelopment Index (IHDI) in 2018-2020. Data Envelopment Analysis is used in this study as a method of measuring the efficiency of each province. This study uses local government spending based on function as an input variable and IHDI indicators which are built based on maqashid sharia in the form of crime rate, national zakat index, life expectancy, the average length of schooling, birth rate, gini ratio, and expenditure per population capita as output variable. The results of this study indicate that the efficiency level of local government spending on the hifdz an-nafs aspect has the highest average efficiency score among other aspects, namely 96-97%. Furthermore, Gorontalo could have gotten a better efficiency score on the hifdz al-’aql indicator.